PENGARUH KUALITAS PRODUK DAN CITRA PRODUK TERHADAP KEPUASAN KONSUMEN PENGGUNA PRODUK IM3 INDOSAT DI KOTA KUDUS - Muhammad Febrian, 09.05.51.0063 (Students Journal of Economic and Management, 2014)
The purpose of this study was to analyze the effect of product quality and image of the product to consumer satisfaction directly. The hypothesis of this study is the better quality of the product and product image perceived, partially will result in high levels of customer satisfaction. The sampling method used in this study is purposive sampling method with a total sample of 125 respondents. The data were analyzed using factor analysis to test the validity of the statement items, alpha formula croanbach to test the reliability of the instrument, the regression analysis to examine the effect of partially magnitude of each independent variable was tested with the coefficient of determination. The results of the research are : ( 1 ) The results of the statistical calculation by linear regression analysis can be given premises regression equation Y = 0.713 X1 + 0.200 X2 . From the regression equation it is known that the quality of the product , and the product image has a positive effect on customer satisfaction and sigfinikan . ( 2 ) The calculation of the magnitude detreminasi coefficient of 0.767 . This means that the effect of product quality variables ( X1 ) , and the image of the product ( X2 ) jointly influence the customer satisfaction variable ( Y ) was 76.7 % while the remaining 23.3 % is influenced by other variables not included in this study . ( 3 ) The hypothesis that has been done within this study are : A ) There is a positive and significant effect between product quality to customer satisfaction on Indosat IM3 products . B ) There is a positive and significant effect of the image of the product to consumer satisfaction in Indosat IM3 products. Keywords: quality of products and product image